Metformin treatment is not associated with altered PD-L1 expression in diabetic patients with oral squamous cell carcinoma - Mamilos, Andreas; Winter, Lina; Lein, Alexander; Spoerl, Steffen; Ludwig, Nils; Ettl, Tobias; Künzel, Julian; Reichert, Torsten; Spanier, Gerrit; Brochhausen, Christoph (Journal of Clinical Medicine, 2024)
Background: The anti-neoplastic activity of metformin is a subject of current debate. Preclinical data have suggested that metformin enhances PD-L1 anti-tumor effects in various cancer entities by decreasing insulin levels and inducing energetic stress. However, its impact on PD-L1 expression remains unclear in a clinical setting. Therefore, we aim to investigate the impact of metformin treatment in type 2 diabetes mellitus (DM) patients on PD-L1 expression in patients with oral squamous cell carcinoma (OSCC). Methods: We performed a retrospective analysis of patients with DM and OSCC treated at our tertiary referral center over a period of 12 years. The tumor proportion score (TPS), immune cell score (IC), and combined positive score (CPS) were used to quantify PD-L1 expression. PD-L1 expression of patients receiving metformin was compared to a control group without metformin prescription. Results: A total of 68 patients diagnosed with OSCC and DM were analyzed, with 24 receiving and 44 not receiving metformin therapy. No statistically significant differences were identified between the metformin and non-metformin groups for any of the scores (TPS: p = 0.818; IC: p = 0.748; CPS: p = 0.387). Conclusions: In contrast to previous studies, we could not find significant differences in PD-L1 expression between patients with and without metformin intake. Further research needs to shed light on the exact mechanism of metformin in different tumor entities. A comprehensive understanding of metformin’s role in cancer therapy could provide valuable insights for potential use of metformin as an adjuvant treatment to immune checkpoint therapy.
Gesehen am 28.10.2024